MCMC method for Markov mixture simultaneous-equation models: a note - Christopher A. Sims; Tao Zha (Federal Reserve Bank of Atlanta, 2004)
This paper extends the methods developed by Hamilton (1989) and Chib (1996) to identified multiple-equation models. It details how to obtain Bayesian estimation and inference for a class of models with different degrees of time variation and discusses both analytical and computational difficulties.
Keywords: 330; Volatilität; Bayes-Statistik; Markovscher Prozess; Theorie; Simultanes Gleichungssystem